Detecting structural transformation of cobalt phosphonate to active bifunctional catalysts for electrochemical water-splitting - Indra A.; Menezes P.W.; Zaharieva I.; Dau H.; Driess M. (My University, 2025)
In recent years, several cobalt-based catalysts have been developed for water splitting because of their promising activity, stability and structural motifs. Here, we report that cobalt phosphonate represents a novel class of bifunctional single-source precursors for highly efficient alkaline electrochemical O2 evolution (OER) and H2 evolution reaction (HER). Inspired by its favorable catalytic OER and HER activity, an overall water-splitting device has been constructed from this precursor, showing very low cell voltage (1.62 V @ 10 mA cm-2) and excellent long-term stability. Depending on the applied oxidation and reduction potential on cobalt phosphonate, two distinct modified structures at the anode and cathode have been uncovered employing the quasi in situ X-ray absorption spectroscopy and ex situ methods. During OER, the phosphonate precursor reorganized itself to layered CoOx(OH)y structure with defects and disorders, while the contribution of the metallic Co along with Co3O4 spinel and Co(OH)2 is evident to drive the HER. The presented work demonstrates the advantage of using the 'all-in-one' precursor approach to realize bifunctional water-splitting electrocatalysts through the evolution of different species with self-supporting interfacial structural features at the anode and cathode during electrochemical water splitting. © 2020 The Royal Society of Chemistry.